Understanding contrasts in later life migration patterns: Germany, Britain and the United States - Friedrich, Klaus; Warnes, Anthony M. (ERDKUNDE, 2000)
The paper proposes explanations for the strong contrasts among highly developed nations in the migration patterns of older people. It focuses on the relative prevalence of long-distance moves and of migrations to high amenity areas. The argument of the paper draws on recently published analyses of elderly migration in eleven OECD-nations and from the findings of recent studies by the authors. It focuses on two sets of influences upon the relative prevalence of long distance ’amenity-seeking? migrations by older people: cultural and urban-rural differences in people’s ’place identity?, and the ’opportunity sets? of environmentally attractive destinations within and accessible to each nation. As a subsidiary theme, it examines a convergence hypothesis about the evolution of migration among older people, that features now found in North America represent a later stage along a path that Europe has not yet reached but will attain. Under this hypothesis, the much higher rate of long distance mobility and of amenity-seeking moves in North America will be adopted by Europeans. The paper demonstrates substantial differences in ’attachment to place? among older people in Germany compared to the United States. Associations are also shown between the prevalence of internal long distance retirement moves and (a) the availability of environmentally attractive destinations within a country, and (b) the distribution in other countries of close family members. It is concluded that the factors influencing the development of elderly migration and the patterns observed in each country are partly cultural, partly historical and partly environmental, and that there is unlikely to be a single developmental path for migration in later life.